Effects of maternal mild hyperglycemia associated with snack intake on offspring metabolism and behavior across the lifespan - Martins, Marina Galleazzo [UNESP]; Woodside, Barbara; Kiss, Ana Carolina Inhasz [UNESP] (Elsevier, 2024)
The increasing prevalence of diabetes is of particular concern in women of childbearing age because of the short and long-term consequences of maternal diabetes for the health of the offspring, such as a greater risk of developing metabolic impairments and cognitive deficits. In addition, maternal diet during pregnancy and lactation might contribute to preventing or ameliorating adverse offspring outcomes. Recently, we described that access to snacks exacerbates glucose intolerance in mildly hyperglycemic pregnant dams. Therefore, we hypothesized that these offspring would show greater impairment in metabolic and behavioral outcomes across the lifespan. Neonatal STZ treatment was employed to induce maternal mild hyperglycemia in females. After mating, normo- and hyperglycemic dams were given access either to standard chow or standard show plus snacks. Male and female offspring were evaluated on postnatal days (PND) 30, 90, and 360. Offspring behavior was assessed in the marble burying task, the open-field test, the elevated-plus maze, and sucrose preference. Glucose tolerance and morphometric analyses were also carried out. Maternal hyperglycemia increased body weight and fat deposition only on PND 30, while retroperitoneal fat deposition was reduced in the offspring of snack-fed dams. However, maternal snack intake reduced offspring body weight and length on PND 90. Fasting glucose was increased in females born to hyperglycemic, snack-fed dams on PND 90. Glucose clearance was altered by both maternal conditions in male offspring on PND 30, however, this sex difference was reversed on PND 90, with maternal hyperglycemia impairing glucose clearance only in females. In addition, maternal hyperglycemia reduced anxiety-like behavior in female offspring on PND 30, especially in the offspring of snack-fed dams, while maternal snack intake reduced sucrose preference in both males and females in adulthood. These results suggest that the effects of maternal hyperglycemia during pregnancy and lactation on offspring outcomes were not exacerbated by snack intake. Although additive effects of the two maternal conditions were hypothesized, the absence of such effects could be related to the mild maternal hyperglycemia induced by STZ treatment even when combined with snack intake. While maternal hyperglycemia alone impaired some offspring outcomes, its association with snack intake did not aggravate those impairments but rather resulted in outcomes more similar to those of offspring born to normoglycemic dams. Finally, females were found to be more susceptible to both the effects of maternal hyperglycemia and snack intake on metabolism and behavior.
Keywords: Hyperglycemia; Male and female offspring; Offspring behavior; Pregnancy